Thoughts, Labyrinths, and Torii - Maurício Vieira Kritz (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Cognition is addressed since millennia but started to be systematically studied around the middle of last century, together with other intellectual initiatives in its neighbourhood. It has been approached from several perspectives while grounded on several intellectual disciplines, most of them scientific. Yet, there is still no consensus about what a cognitive occurrence or fact is from the scientific point of view. Moreover, cognition is an individualcentred science. This text presents a case-study and advances an empirical conjecture about the relations between mind-processes, brainorganisation, signal-perception, and knowledge-creation. This ansatz is associated with the investigation of cognition and of creative mental processes, without specifically adhering to any of the current approaches regarding these subjects. It was suggested by a personal experience and can only be adequately expressed with the aid of ideas emanating from that experience. The ansatz is thus uncommitted to existing approaches, touching nevertheless most of them. To motivate and put things in context, we tell a true story centred on mental states and recalled from the mists of time, of which I hold the key. The description of what goes on inside our minds is though. We address this puzzle using allegories and metaphors, particularly three: thoughts as self-dialogues, labyrinths as in any game, and Torii the Japanese portals separating laic from sacred things. We also discuss how the three mental entities represented by them interact and stand in relation to each another.